News Consumption on Social Media: Associated Factors in Peru - Pacheco, Edgar (2025)
Social media has established itself as an important source for accessing information and news. Although international studies have explored the impact of these platforms, research in Peru is still scarce. The objective of this study is to investigate whether the variables of gender and age are statistically associated with news consumption on social media. Using a representative sample of the online adult population (N = 2005), this article focuses on six platforms: Facebook, YouTube, Instagram, X (formerly Twitter), TikTok, and WhatsApp. The descriptive and inferential analysis, based on the Rao-Scott chi-square statistical test, revealed significant differences by gender on most of the examined platforms, with male users preferring YouTube and X for news consumption, and the female segment leaning towards TikTok and Instagram. The study also found differences according to age. Facebook and YouTube emerged as the dominant platforms for accessing news, particularly among older age groups, while TikTok showed a predominant trend among young people aged 18 to 29. These results underscore the complexity and dynamism of news consumption media repertoires in the digital age and the importance of considering demographic factors as key variables in the context of Peru.